2021
DOI: 10.3390/nu13051598
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Vitamin E Level Associated with Low Hand Grip Strength in Community-Dwelling Adults: Korean National Health and Nutrition Examination Survey (KNHANES VII) 2016–2018

Abstract: This study assessed the association between serum vitamin E levels and hand grip strength (HGS) in community-dwelling adults data of 1011 men aged 50 years and older and 1144 postmenopausal women were analyzed. Low HGS was defined as HGS below the sex-stratified median value. Proportion of low HGS was the greatest in the lowest quintile of serum vitamin E level (<10.51 mg/L, 57.1%), with a decreasing trend toward the highest vitamin E quintile (>17.81 mg/L, 43.6%; p < 0.001). A one-unit (mg/L) decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Micronutrients are critical for physiological functions of human being, and recent studies have found potential associations between micronutrients and muscle performance in elderly individuals (7,8). The associations between disturbances of several serum micronutrients (calcium, magnesium, selenium, copper, iron, zinc, Vitamin A, Vitamin B12, Vitamin D, and Vitamin E) and sarcopenia have been identified in previous observational studies, but the findings are controversial (6,(9)(10)(11)(12)(13)(14)(15)(16). Besides, given the observational design of these studies, the causal relationships between the levels of aforementioned serum micronutrients and the risk of sarcopenia remained unknown to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrients are critical for physiological functions of human being, and recent studies have found potential associations between micronutrients and muscle performance in elderly individuals (7,8). The associations between disturbances of several serum micronutrients (calcium, magnesium, selenium, copper, iron, zinc, Vitamin A, Vitamin B12, Vitamin D, and Vitamin E) and sarcopenia have been identified in previous observational studies, but the findings are controversial (6,(9)(10)(11)(12)(13)(14)(15)(16). Besides, given the observational design of these studies, the causal relationships between the levels of aforementioned serum micronutrients and the risk of sarcopenia remained unknown to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not find any RCTs in Asia that directly evaluated vitamin E supplementation in terms of muscle health outcomes. Two cross‐sectional studies examined serum levels and dietary vitamin E but provided inconclusive evidence for vitamin E supplementation 86,87 . Therefore, evidence to support a role of vitamin supplementation in Asian studies was only found for vitamin D. Please see Table 1, Consensus Statement 8.…”
Section: Nutritional Supplementationmentioning
confidence: 99%
“…Two cross-sectional studies examined serum levels and dietary vitamin E but provided inconclusive evidence for vitamin E supplementation. 86,87 Therefore, evidence to support a role of vitamin supplementation in Asian studies was only found for vitamin D. Please see…”
Section: Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, higher vitamin E levels are related to handgrip strength in Korean young adults (≤40 years) but not in older adults (40 years) [ 10 ]. However, other studies using Korean adults showed an association between vitamin E and handgrip strength in those aged 50 years and older [ 11 ]. Small group studies have shown that folic acid affects handgrip strength [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 96%